2021
DOI: 10.3390/md19040225
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Source Quorum Quenching Enzyme YtnP to Improve Hygiene Quality in Dental Units

Abstract: Biofilm in dental unit water lines may pose a health risk to patients and dental practitioners. An AdiC-like quorum quenching enzyme, YtnP, was cloned from a deep-sea probiotic Bacillus velezensis, and heterologously expressed in E. coli to examine the application on the improvement of hygiene problems caused by biofilm infection of Pseudomonas aeruginosa in dental units. Pseudomonas bacteria were isolated from dental chair units and used to grow static biofilms in the laboratory. A water filter system was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…These marine metabolites are thought to be promising leads for inhibition of the main protease, which plays an important role in the life cycle of the virus. Similarly, Gentile et al identified seventeen potential M pro inhibitors from the class phlorotannins isolated from Sargassum spinuligerum brown algea [ 30 ]. Docking energies ranged from −14.6 to −10.7 kcal/mol and the compounds interacted with M pro through extensive hydrogen bonding as well as hydrophobic interactions.…”
Section: Promising Compounds From Marine Algae Bacteria Sponges and Fish For Covid-19 Treatmentmentioning
confidence: 99%
See 4 more Smart Citations
“…These marine metabolites are thought to be promising leads for inhibition of the main protease, which plays an important role in the life cycle of the virus. Similarly, Gentile et al identified seventeen potential M pro inhibitors from the class phlorotannins isolated from Sargassum spinuligerum brown algea [ 30 ]. Docking energies ranged from −14.6 to −10.7 kcal/mol and the compounds interacted with M pro through extensive hydrogen bonding as well as hydrophobic interactions.…”
Section: Promising Compounds From Marine Algae Bacteria Sponges and Fish For Covid-19 Treatmentmentioning
confidence: 99%
“…Docking energies ranged from −14.6 to −10.7 kcal/mol and the compounds interacted with M pro through extensive hydrogen bonding as well as hydrophobic interactions. In addition, the Sars-Cov-2 RNA polymerase along with nsp7/8 are required for the RNA replication and viral protein synthesis [ 30 ]. Remdesivir is a known inhibitor of the RNA dependent-RNA polymerase, and three marine Scleractinia metabolites were found to bind the polymerase in the same position as Remdesivir [ 6 , 7 , 8 , 30 ].…”
Section: Promising Compounds From Marine Algae Bacteria Sponges and Fish For Covid-19 Treatmentmentioning
confidence: 99%
See 3 more Smart Citations